Unlocking the Syariah Insurance Market in Indonesia: Overcoming Barriers and Enhancing Market Penetration - Ronaldo, Reza; Rizal, Muhamad; Maulini, Yul (CV. Kalimasada Group, 2024)
As the largest Muslim-majority country, Indonesia has significant potential for Syariah insurance (Takaful). However, its market penetration remains below 10% due to low financial literacy, regulatory fragmentation, and limited product innovation. This study employs qualitative thematic analysis through expert interviews and document analysis to explore the key challenges and strategic interventions needed to enhance Syariah insurance adoption. Findings reveal that digital transformation, regulatory harmonization, and financial literacy programs are crucial for sustainable growth. Lessons from Malaysia and GCC countries indicate that fintech-driven Syariah insurance solutions, such as blockchain-based takaful and AI-powered underwriting, can significantly increase accessibility and efficiency. This study proposes a regulatory alignment framework, fintech adoption strategies, and microtakaful expansion to enhance market inclusion. The results contribute to the academic discourse by providing a roadmap for policymakers, insurers, and financial regulators to strengthen Indonesia’s Syariah insurance ecosystem.